Wellens syndrome or For whom the bell tolls? - Yu.V. Savitska; A.I. Klantsa; N.V. Shchepina (Кардіохірургія та інтервенційна кардіологія)
Wellens syndrome is an electrocardiographic pattern associated with acute stenosis of the proximal part of the left anterior descending artery, a high risk of anterior myocardial infarction and sudden cardiac death from fatal arrhythmias. Detection of this syndrome will significantly reduce the risk of an acute event.